2015
DOI: 10.1111/pan.12678
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting a measure of child postoperative recovery: development of the Post Hospitalization Behavior Questionnaire for Ambulatory Surgery

Abstract: Background The Post Hospitalization Behavior Questionnaire (PHBQ) was designed for assessing children’s post-hospitalization and postoperative new-onset behavioral changes. However, the psychometric properties of the scale have not been re-evaluated in the past five decades despite substantial changes in the practice of surgery. In this investigation, we examined the psychometric properties of the PHBQ to potentially increase the efficacy and relevance of the instrument in current perioperative settings. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 26 publications
(44 reference statements)
0
38
0
1
Order By: Relevance
“…The mYPAS‐SF consists of 18 items in 4 domains of behavior (activity, emotional expressivity, state of arousal, and vocalization). All mYPAS domains have good to excellent inter and intraobserver reliability using Kappa statistics (.73‐.91) and has good face validity . Total scores range from 23.3 to 100 with higher scores indicating a higher level of anxiety.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mYPAS‐SF consists of 18 items in 4 domains of behavior (activity, emotional expressivity, state of arousal, and vocalization). All mYPAS domains have good to excellent inter and intraobserver reliability using Kappa statistics (.73‐.91) and has good face validity . Total scores range from 23.3 to 100 with higher scores indicating a higher level of anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…Total scores range from 23.3 to 100 with higher scores indicating a higher level of anxiety. Moreover, the mYPAS demonstrated strong criterion validity . The measure has been used extensively in studies in various fields including psychology, surgery, anesthesia, and dentistry, and has been used in over 12 different languages including Spanish, Danish, and Swedish and in 14 different countries including Spain, Israel, and Portugal.…”
Section: Methodsmentioning
confidence: 99%
“…It was advised that researchers score the measure by taking an average of the individual items. Notably, this version of the PHBQ still lacks meaningful clinical cutoff scores and is specifically designed for ambulatory surgeries …”
Section: Future Directionsmentioning
confidence: 99%
“…1,[5][6][7]10,13,22 Furthermore, previous overviews of behavioural changes in children after hospitalization have concluded that anaesthesia-related techniques, medication and events are not the only contributors to the overall experience of hospitalization. 1,[5][6][7]10,13,22 Furthermore, previous overviews of behavioural changes in children after hospitalization have concluded that anaesthesia-related techniques, medication and events are not the only contributors to the overall experience of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Maladaptive behaviour like night-time crying, separation anxiety, temper tantrums, enuresis, general anxiety or poor appetite have been described in up to 50% of paediatric patients after general anaesthesia. 1,2 Maladaptive behaviour like night-time crying, separation anxiety, temper tantrums, enuresis, general anxiety or poor appetite have been described in up to 50% of paediatric patients after general anaesthesia.…”
Section: Editorial Commentmentioning
confidence: 99%